Pengungkapan Diri Muslimah Bercadar melalui Instagram: Pendekatan Fenomenologi - Yopi Kusmiati; Rayhan Bayruni (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2020)
Nowdays the hijrah culture is becoming a trend. Not a few Muslim women who emigrated by wearing the veil as a face covering, but then it became a challenge for them when they get discrimination, which is linked to terrorism. The phenomenon of veiled Muslim women in Indonesia continues to increase until it has become a trendy outfit as evidenced by the number of veiled Muslim women who are increasingly open on Instagram in expressing themselves. This study uses a constructivist paradigm with qualitative methods and a phenomenological approach. The subject of the study is five Muslimah Instagram users. This study found that there was expressive self-disclosure with enlarged open areas (open self) and Islamic self-disclosure with enlarged hidden self areas. There are functions of expression, self validation, social control and relationship development experienced by veiled Muslim women, and there is no function of self clarification.  This study concluded that Muslims on Instagram can influence the community in removing the negative stigma of muslims and giving direction to other muslims to stay open and not shut away from society.